Electrolyte and battery
By combining vinyl sulfite and chain carbonate with lithium difluorosulfonimide in lithium-ion battery electrolyte, a low-impedance SEI film is solved, and the viscosity increase and ionic conductivity of the electrolyte under low temperature conditions is solved. The problem of reduction improves the battery's magnification and low-temperature performance.
Patent Information
- Application Number
- CN202310570162.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-19
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-05-19
AI Technical Summary
The viscosity of existing lithium-ion battery electrolyte increases and the ionic conductivity decreases under low temperature conditions, resulting in poor low-temperature performance and rate performance of the battery, and limited improvement of existing additives.
Vinyl sulfite, chain carbonate or chain carboxylic acid esters are used to form a low-impedance SEI film to improve the ionic conductivity of the electrolyte and the rate performance of the battery.
It significantly improves the battery's rate performance and low-temperature performance, ensuring the battery's capacity retention and high-temperature cycling performance in low-temperature environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to an electrolyte and a battery. Background Art
[0002] Ethylene carbonate (EC) is an important solvent component in the electrolyte because of its excellent film-forming ability on the graphite surface and high dissociation ability for lithium salts. Currently, commercial lithium-ion battery electrolyte solvents usually contain ≥30% EC by mass. However, due to the high melting point of EC at 36.4°C, the viscosity of the electrolyte increases rapidly at low temperatures, the ionic conductivity decreases, and the desolvation barrier increases, limiting the low-temperature performance of lithium-ion batteries. In addition, the SEI film generated by EC-based electrolytes on the negative electrode surface has a large impedance, which limits the battery rate performance.
[0003] In the prior art, the method of introducing additives is often used to improve the low-temperature performance of the electrolyte and reduce the internal resistance of the electrode. For example, CN 108321433 A discloses an electrolyte additive and an electrolyte that can improve the low-temperature performance of a lithium-ion battery. The additive is pyridine containing an electron-donating group substituent, and its molecular structure does not contain a strong electron-withdrawing group substituent. When the additive is added to the electrolyte, the normal temperature and high temperature performance of the battery are not affected, while the low temperature performance is effectively improved.
[0004] For example, CN113851718A discloses an electrolyte additive and electrolyte that can improve the low-temperature performance of lithium batteries. The additive can be decomposed before the electrolyte solvent and form a thin and continuous SEI film in the lithium battery. Compared with the SEI film formed by traditional electrolytes, the main component of the film has lower impedance and better conductivity; it can prevent the oxidative decomposition of the electrolyte on the surface of the positive electrode material under low temperature conditions, thereby improving the low-temperature performance of the electrolyte.
[0005] However, the electrolytes described in the above patents all have a relatively high content of ethylene carbonate added thereto, and then the low temperature performance of the battery is improved by adding external additives, which can improve the performance to a certain extent, but cannot fundamentally solve the problems caused by EC.
[0006] Therefore, developing an electrolyte without adding ethylene carbonate, having high ionic conductivity, and being able to ensure low internal resistance, excellent rate and low temperature characteristics of the battery is an urgent problem to be solved in this field. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention aims to provide an electrolyte and a battery. The electrolyte is a compound of a specific type of organic solvent and a specific type of lithium salt, so that the electrolyte has high ion conductivity, the impedance of the SEI film formed on the electrode surface is low, the rate performance and high temperature performance of the battery are improved, and the battery has excellent capacity retention when used in a low temperature environment.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides an electrolyte, the electrolyte comprising an organic solvent and a lithium salt; the organic solvent comprising a first solvent and a second solvent; the first solvent comprising vinyl sulfite; the second solvent comprising a chain carbonate and / or a chain carboxylate; the lithium salt comprising a main salt and an auxiliary salt; the main salt comprising lithium bis(fluorosulfonyl)imide; based on the mass of the electrolyte being 100%, the mass percentage of the first solvent is 20 to 60%.
[0010] In the present invention, the viscosity and melting point of ethylene sulfite (ES) are significantly lower than those of ethylene carbonate (EC), and ES can form a low-impedance SEI (reduced to generate a SEI component with high ionic conductivity) on the surface of the negative electrode, so that the rate performance and low-temperature performance of the battery can be significantly improved; the chain carbonate and / or chain carboxylic acid ester has a smaller viscosity, excellent electrochemical stability, and provides a certain lithium salt dissociation ability, which can play a role in improving the low-temperature characteristics of the battery; lithium bis(fluorosulfonyl)imide (LiFSI) is easier to dissociate into free lithium ions than other lithium salts, so that the electrolyte obtains a higher ionic conductivity, effectively ensuring the high-rate characteristics of the battery. The electrolyte is compounded with a high content of ethylene sulfite (ES) and a chain carbonate and / or a chain carboxylate through an organic solvent, and lithium bis(fluorosulfonyl)imide is used as a main salt, so as to provide high ionic conductivity within a wide temperature range and ensure smooth migration of lithium ions; at the same time, a SEI film rich in components such as lithium sulfide and lithium fluoride is formed on the surface of the negative electrode to maintain the interfacial stability during the electrochemical cycle, thereby achieving excellent rate and low-temperature performance, and effectively solving the problem that the viscosity of the electrolyte increases rapidly and the ionic conductivity decreases under low temperature conditions due to the use of ethylene carbonate, thereby leading to poor battery rate performance.
[0011] Taking the mass of the electrolyte as 100%, the mass percentage of the first solvent is 20-60%, for example, it can be 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 52%, 54%, 56%, 58%, 60%, etc.
[0012] In the present invention, within the mass range defined above, the first solvent can ensure excellent lithium salt dissociation degree, while forming a Li2S-rich SEI film to provide a fast transmission channel for lithium ions at the interface.
[0013] Preferably, based on the mass of the electrolyte as 100%, the mass percentage of the second solvent is 30-50%, for example, it can be 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, etc.
[0014] Preferably, the mass ratio of the first solvent to the second solvent is (0.4-2.0):1, for example, 0.4:1, 0.42:1, 0.45:1, 0.48:1, 0.5:1, 0.52:1, 0.55:1, 0.58:1, 0.6:1, 0.62:1, 0.65:1, 0.68:1, 0.7:1, 0.72:1, 0.75:1, 0.78:1, 0.8:1, 0.82:1, 0.85:1 , 0.9:1, 0.95:1, 1:1, 1.12:1, 1.15:1, 1.18:1, 1.2:1, 1.22:1, 1.25:1, 1.28:1, 1.3:1, 1.32:1, 1.35:1, 1.4:1, 1.45:1, 1.5:1, 1.55:1, 1.6:1, 1.65:1, 1.7:1, 1.8:1, 1.85:1, 1.9:1, 1.95:1, 2.0:1, etc.
[0015] In the present invention, when the mass ratio of the first solvent to the second solvent is low, on the one hand, it cannot provide a sufficiently high dielectric constant to promote the dissociation of lithium salts, and on the other hand, it cannot provide enough inorganic components with high ionic conductivity in SEI, and cannot ensure low interfacial impedance at a large rate; when the mass ratio of the first solvent to the second solvent is high, it may lead to an increase in the thickness of SEI, which in turn reduces the transmission capacity of lithium ions at the interface.
[0016] Preferably, the linear carbonate includes at least one of dimethyl carbonate, diethyl carbonate or ethyl methyl carbonate.
[0017] Preferably, the chain carboxylic acid ester includes at least one of ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate or propyl propionate.
[0018] Preferably, based on the mass of the electrolyte as 100%, the mass percentage of the main salt is 8-16%, for example, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, etc.
[0019] In the present invention, the main salt content can ensure excellent ionic conductivity within the above-defined range; when the main salt content is too low, the concentration of dissociated free lithium ions becomes low, affecting the ionic conductivity of the electrolyte; when the main salt content is too high, the viscosity of the electrolyte will increase, which is not conducive to the migration of lithium ions and reduces the wettability of the electrolyte to the electrode material.
[0020] The mass percentage of the auxiliary salt is 2-8%, for example, it can be 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, etc.
[0021] Preferably, the mass ratio of the main salt to the auxiliary salt is (1.0-8.0):1, for example, it can be 1.0:1, 1.02:1, 1.04:1, 1.06:1, 1.08:1, 1.1:1, 1.12:1, 1.14:1, 1.16:1, 1.18:1, 1.2:1, 1.22:1, 1.24:1, 1.26:1, 1.28:1, 1.3:1, 1.32:1, 1.35:1, 1.38:1, 1.4:1, 1.42:1, 1.45:1, 1.48:1, 1.5:1, 1 :1, and more preferably (5 to 7.5):1.
[0022] In the present invention, the mass ratio of the main salt and the auxiliary salt can play a good synergistic role within the above-defined range; when the mass ratio of the main salt and the auxiliary salt is low, the number of free lithium ions in the dissociated state may decrease, affecting the ionic conductivity of the electrolyte; when the mass ratio of the main salt and the auxiliary salt is high, the passivation protection effect on the positive electrode aluminum collector becomes worse, and when charging to a high voltage, the positive electrode collector will be corroded.
[0023] Preferably, the auxiliary salt includes at least one of lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium difluorobisoxalatephosphate, lithium tetrafluorooxalatephosphate or lithium difluorobisoxalatephosphate.
[0024] In the present invention, the auxiliary salt is preferably lithium difluorooxalatoborate (LiDFOB) or lithium difluorooxalatophosphate (LiDFOP), and the main salt lithium bis(fluorosulfonyl)imide is matched with the auxiliary salt lithium difluorooxalatoborate or lithium difluorooxalatophosphate to effectively improve the rate and low temperature performance of the battery cell. The main salt LiFSI has excellent dissociation ability in the solvent, can provide a higher ionic conductivity for the electrolyte, and LiFSI decomposes on the surface of the negative electrode to form an inorganic-rich SEI film. After LiDFOB and LiDFOP dissociate, a passivation layer will be formed on the surface of the aluminum current collector, which plays a role in protecting the current collector and avoiding oxidative decomposition of the electrolyte; at the same time, LiDFOB and LiDFOP have lower viscosity and better ionic conductivity under low temperature conditions, and their anions are reduced to help generate a low-resistivity SEI film.
[0025] Preferably, based on the mass of the electrolyte as 100%, the electrolyte also includes 0.1-15% additives, for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, etc.
[0026] Preferably, the additive includes at least one of a fluorocarbonate, an unsaturated cyclic carbonate, a cyclic sultone, a cyclic sulfate or a lithium salt additive.
[0027] In the present invention, the fluorocarbonate includes at least one of fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC) or trifluoropropylene carbonate (TFPC). The unsaturated cyclic carbonate includes but is not limited to vinylene carbonate (VC), vinyl ethylene carbonate (VEC), etc. The cyclic sultone includes but is not limited to 1,3-propane sultone (PS), and the lithium salt additive includes but is not limited to lithium difluorophosphate (LiPO2F2); the additive also includes one or more of vinyl sulfate, LiNO3, 1,2,3,6-tetrahydrophthalic anhydride (THPA), succinic anhydride (SA), and tris(trimethylsilyl) phosphate (TMSP).
[0028] In the present invention, the preferred additive is VC. After adding VC, a free radical polymerization reaction can occur on the surface of the negative electrode to form a flexible SEI film containing components such as polyvinyl carbonate and alkyl lithium carbonate, which effectively isolates the electrolyte and electrode side reactions and improves the stability of the negative electrode interface.
[0029] In a second aspect, the present invention provides a battery, comprising the electrolyte as described in the first aspect.
[0030] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The electrolyte provided by the present invention has an organic solvent that is a compound of high-content vinyl sulfite and chain carbonate and / or chain carboxylate, and lithium bis(fluorosulfonyl)imide is used as a main salt and a supplementary salt, so that the ion conductivity of the electrolyte is high, the internal resistance of the electrode is reduced, and the rate performance, high-temperature cycle performance and low-temperature discharge performance of the battery are improved. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0034] Example 1
[0035] This embodiment provides an electrolyte, which includes, by mass percentage, 45.7% of vinyl sulfite, 32.4% of ethyl methyl carbonate, 8.8% of lithium bis(fluorosulfonyl)imide, 7.1% of lithium hexafluorophosphate, 1% of vinylene carbonate and 5% of fluoroethylene carbonate.
[0036] The electrolyte is prepared by the following method: specifically, vinyl sulfite, ethyl methyl carbonate, lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, vinylene carbonate and fluoroethylene carbonate are uniformly mixed according to the formula amount to obtain the electrolyte with a water content of less than 20 ppm.
[0037] Example 2
[0038] This embodiment provides an electrolyte, which includes, by mass percentage, 32% of vinyl sulfite, 45.3% of ethyl methyl carbonate, 9.2% of lithium bis(fluorosulfonyl)imide, 7.5% of lithium hexafluorophosphate, 1% of vinylene carbonate and 5% of fluoroethylene carbonate.
[0039] The preparation method of the electrolyte in this embodiment is the same as that in Embodiment 1.
[0040] Example 3
[0041] This embodiment provides an electrolyte, which includes, by weight percentage, 48.2% vinyl sulfite, 34.1% ethyl methyl carbonate, 14.5% lithium bis(fluorosulfonyl)imide, 2.2% lithium difluorooxalatoborate, and 1% vinylene carbonate.
[0042] The preparation method of the electrolyte in this embodiment is the same as that in Embodiment 1.
[0043] Example 4
[0044] This embodiment provides an electrolyte, which includes, by mass percentage, 33.7% vinyl sulfite, 47.8% ethyl methyl carbonate, 15.2% lithium bis(fluorosulfonyl)imide, 2.3% lithium difluorooxalatoborate, and 1% vinylene carbonate.
[0045] The preparation method of the electrolyte in this embodiment is the same as that in Embodiment 1.
[0046] Example 5
[0047] This embodiment provides an electrolyte, which includes, by mass percentage, 33.3% vinyl sulfite, 47.2% ethyl methyl carbonate, 15.2% lithium bis(fluorosulfonyl)imide, 2.3% lithium difluorooxalatoborate, 1% vinylene carbonate and 1% lithium difluorophosphate.
[0048] The preparation method of the electrolyte in this embodiment is the same as that in Embodiment 1.
[0049] Example 6
[0050] This embodiment provides an electrolyte, which includes, by weight percentage, 45.8% vinyl sulfite, 40% dimethyl carbonate, 11.2% lithium bis(fluorosulfonyl)imide, 2% lithium difluorooxalatoborate, and 1% vinylene carbonate.
[0051] The preparation method of the electrolyte in this embodiment is the same as that in Embodiment 1.
[0052] Example 7
[0053] This embodiment provides an electrolyte, which includes, by weight percentage, 46% vinyl sulfite, 36% dimethyl carbonate, 14% lithium bis(fluorosulfonyl)imide, 2% lithium difluorobis(oxalyl)phosphate, and 2% vinylene carbonate.
[0054] The preparation method of the electrolyte in this embodiment is the same as that in Embodiment 1.
[0055] Example 8
[0056] This embodiment provides an electrolyte, which differs from the embodiment 3 only in that 34.1% of ethyl methyl carbonate is replaced by 17% of dimethyl carbonate and 17.1% of propyl acetate, and the other components, amounts and preparation methods are the same as those in the embodiment 3.
[0057] Example 9
[0058] This embodiment provides an electrolyte, which is different from Embodiment 3 only in that the total amount of lithium bis(fluorosulfonyl)imide and lithium difluorooxalatoborate remains unchanged, with a mass ratio of 3:1, and other components, amounts and preparation methods are the same as those in Embodiment 3.
[0059] Example 10
[0060] This embodiment provides an electrolyte, which is different from the embodiment 3 only in that the total amount of lithium bis(fluorosulfonyl)imide and lithium difluorooxalatoborate remains unchanged, with a mass ratio of 8:1, and the other components, amounts and preparation methods are the same as those in the embodiment 3.
[0061] Embodiment 11
[0062] This embodiment provides an electrolyte, which is different from the embodiment 3 only in that the total amount of vinyl sulfite and ethyl methyl carbonate remains unchanged, with a mass ratio of 0.5:1, and the other components, amounts and preparation methods are the same as those in the embodiment 3.
[0063] Example 12
[0064] This embodiment provides an electrolyte, which is different from Embodiment 3 only in that the total amount of vinyl sulfite and ethyl methyl carbonate remains unchanged, with a mass ratio of 1.8:1, and other components, amounts and preparation methods are the same as those in Embodiment 3.
[0065] Example 13
[0066] This embodiment provides an electrolyte, which differs from Embodiment 3 only in that the total amount of the organic solvent remains unchanged, the ratio of vinyl sulfite to ethyl methyl carbonate remains unchanged, the organic solvent further includes 20% vinyl carbonate, and the other components, amounts and preparation methods are the same as those in Embodiment 3.
[0067] Comparative Example 1
[0068] This comparative example provides an electrolyte, which differs from Example 3 only in that the vinyl sulfite is replaced by an equal mass of dimethyl sulfite, and the other components, amounts and preparation methods are the same as those in Example 3.
[0069] Comparative Example 2
[0070] This comparative example provides an electrolyte, which is different from Example 3 only in that the total amount of the organic solvent remains unchanged, the content of vinyl sulfite is 15%, and the other components, amounts and preparation methods are the same as those in Example 3.
[0071] Comparative Example 3
[0072] This comparative example provides an electrolyte, which differs from Example 3 only in that the vinyl sulfite is replaced by an equal amount of vinyl carbonate, the total amount of the lithium salt remains unchanged, namely, lithium hexafluorophosphate, and the other components, amounts and preparation methods are the same as those in Example 3.
[0073] Performance Testing
[0074] A high-nickel (Ni>80%) NCM positive electrode sheet, a graphite negative electrode sheet and a polyethylene separator were assembled into a soft-pack core, and the electrolytes provided in Examples 1 to 13 and Comparative Examples 1 to 3 were injected respectively to prepare soft-pack cells, and the cells were tested for rate performance, low-temperature discharge, and 45°C cycle performance; the specific test methods are as follows:
[0075] (1) Ionic conductivity:
[0076] The ionic conductivity of the electrolyte was tested using a Wan Tong 914 conductivity meter. Standard reagents were used for calibration before the experiment, and then the ionic conductivity test was performed at 25°C.
[0077] (2) Internal resistance after capacitance division:
[0078] The formed battery was fully charged using a 0.15C constant current and constant voltage method, and then discharged using a 0.33C constant current. After discharge, the AC impedance of the battery cell was tested (@1K Hz).
[0079] (3) Rate performance:
[0080] The battery was charged at 1C, 2C and 3C and discharged at 0.33C in the double charge test; the battery was charged at 0.33C and discharged at 1C, 2C and 3C in the double discharge test.
[0081] (4) Low temperature discharge performance:
[0082] Charge and discharge once at 0.2C at 25℃, use constant current and constant voltage to charge and constant current to discharge, and record the discharge capacity; then charge at 0.2C constant current and constant voltage at 25℃ to the cut-off voltage (cut-off current is 0.05C); put the battery in a -20℃ low-temperature box, leave it for 24h, and then discharge it at 0.2C current and constant current to the cut-off voltage, and record the discharge capacity.
[0083] (5) High temperature cycle performance:
[0084] The battery was charged at 1C using a constant current and constant voltage method (cut-off current 0.05C), left for 10 minutes, and then discharged at 1C using a constant current method and left for 10 minutes; the battery cell was cycled at 45°C.
[0085] The specific test results are shown in Table 1:
[0086] Table 1
[0087]
[0088] As can be seen from the above table, the electrolyte provided by the present invention uses a high content of vinyl sulfite and a chain carbonate and / or a chain carboxylate as an organic solvent, and lithium bis(fluorosulfonyl)imide is used as the main salt and the auxiliary salt, so that the ionic conductivity of the electrolyte is high, the internal resistance of the electrode is reduced, and the rate performance, high temperature cycle performance and low temperature discharge performance of the battery are improved. As can be seen from Examples 1 to 8, the ionic conductivity of the electrolyte is 8.74 to 10.26 mS / cm, the internal resistance is low, which is 229.2 to 262.8 mΩ, the -20°C discharge capacity retention rate is 71.8 to 90.1%, and the number of cycles of 80% cycle capacity retention rate at 45°C is 316 to 543 cycles. In the formula of the present invention, when the lithium salt is selected from lithium bis(fluorosulfonyl)imide and lithium difluoro oxalate borate or lithium difluoro dioxalate phosphate, and the additive is selected from vinylene carbonate, the ionic conductivity is higher, the internal resistance is lower, and the low temperature discharge performance and high temperature cycle performance are better.
[0089] It can be seen from Examples 3 and 9 to 13 that if the lithium salt or organic solvent has a non-specific composition and ratio, the ionic conductivity is reduced, and the low-temperature discharge performance and high-temperature cycle performance are deteriorated. Compared with Example 3, it can be seen that the electrolyte of Example 13 contains a high content of ethylene carbonate, and its rate performance, low-temperature discharge performance and high-temperature cycle performance are deteriorated.
[0090] It can be seen from Example 3 and the comparative example that it is not a specific solution of the present application, the ionic conductivity is reduced, and the rate performance, low-temperature discharge performance and high-temperature cycle performance are poor.
[0091] In summary, the electrolyte provided by the present invention uses a new solvent, vinyl sulfite, to replace vinyl carbonate, and selects a specific type of organic solvent and a specific type of lithium salt to compound, so that the ionic conductivity of the electrolyte is high, and the impedance of the SEI film formed on the electrode surface is low, thereby improving the rate performance and low-temperature performance of the battery, and having an excellent capacity retention rate when used in a low-temperature environment, thereby solving the problem that the viscosity of the electrolyte increases rapidly and the ionic conductivity decreases under low temperature conditions due to the use of vinyl carbonate, thereby causing poor battery rate performance.
[0092] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An electrolyte, characterized in that: The electrolyte includes an organic solvent and a lithium salt; The organic solvent includes a first solvent and a second solvent; the first solvent is vinyl sulfite; the second solvent is a chain carbonate and / or a chain carboxylate; The mass ratio of the first solvent to the second solvent is 0.4 to 2.0:1; The lithium salt comprises a main salt and an auxiliary salt; the main salt is lithium bis(fluorosulfonyl)imide; the auxiliary salt is at least one of lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium difluorobis(oxalatophosphate), lithium tetrafluorobis(oxalatophosphate) or lithium difluorobis(oxalatophosphate); The mass ratio of the main salt to the auxiliary salt is 1.0 to 8.0:1; Taking the mass of the electrolyte as 100%, the mass percentage of the first solvent is 20-60%.
2. The electrolyte according to claim 1, characterized in that Taking the mass of the electrolyte as 100%, the mass percentage of the second solvent is 30-50%.
3. The electrolyte according to claim 1, characterized in that The chain carbonate includes at least one of dimethyl carbonate, diethyl carbonate or ethyl methyl carbonate.
4. The electrolyte according to claim 1, characterized in that The chain carboxylic acid ester includes at least one of ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate or propyl propionate.
5. The electrolyte according to claim 1, characterized in that Taking the mass of the electrolyte as 100%, the mass percentage of the main salt is 8-16%, and the mass percentage of the auxiliary salt is 2-8%.
6. The electrolyte according to claim 1, characterized in that The mass ratio of the main salt to the auxiliary salt is 5 to 7.5:
1.
7. The electrolyte according to claim 1, characterized in that Taking the mass of the electrolyte as 100%, the electrolyte further comprises 0.1 to 15% of additives.
8. The electrolyte according to claim 7, characterized in that The additive includes at least one of a fluorinated carbonate, an unsaturated cyclic carbonate, a cyclic sultone, a cyclic sulfate or a lithium salt additive.
9. A battery, characterized in that: The battery comprises the electrolyte according to any one of claims 1 to 8.
